Predictors of Survival in Heart Failure - Yüksel Çavuşoğlu (KARE Publishing, 2015)
Heart failure (HF) is a common clinical syndrome associated with an increased risk of mortality. Although, in general, the 1-year mortality rate is reported as 17% in acute HF patients and 7% in chronic HF patients, it largely depends on the severity of the disease and the implementation of appropriate medical therapy.[1] Identifying those patients who have a poor prognosis and for whom intensive pharmacological or device therapy would be most beneficial is of special importance in HF management. Many clinical and laboratory parameters have been identified in predicting survival in patients with HF due to systolic dysfunction (Table 1). The most frequently used predictors of survival are direct or indirect measures of the severity of cardiac dysfunction. In addition to these cardiac parameters, comorbid conditions and the underlying cause of HF are known to be important determinants of poor prognosis.